2023
DOI: 10.1021/acsami.3c01275
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Binding Mechanisms of Quartz-Selective Peptides: Toward Greener Flotation Processes

Abstract: Mining practices, chiefly froth flotation, are being critically reassessed to replace their use of biohazardous chemical reagents in favor of biofriendly alternatives as a path toward green processes. In this regard, this study aimed at evaluating the interactions of peptides, as potential floatation collectors, with quartz using phage display and molecular dynamics (MD) simulations. Quartz-selective peptide sequences were initially identified by phage display at pH = 9 and further modeled by a robust simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Very recently, a robust simulation scheme combining classical MD, replica exchange MD, and steered MD was synergized to characterize the quartz-selective peptide sequences initially identified by phage display at pH 9 as alternative reagents for direct flotation of quartz mineral. 186 The simulation results revealed that the simultaneous presence of positively and negatively charged residues in peptide sequences are favorable for stronger binding of peptides to the surface due to two main reasons. First, the negatively charged residues have strong affinities toward abundant positively charged moieties on quartz surface at basic pH, and second, the repulsive self-interactions in the peptide chain containing dissimilarly charged residues keep the extended conformation of the peptide, guaranteeing the accessibility of peptide side groups to the surface.…”
Section: Rational Design Of Novel Ecofriendly Collectorsmentioning
confidence: 98%
See 3 more Smart Citations
“…Very recently, a robust simulation scheme combining classical MD, replica exchange MD, and steered MD was synergized to characterize the quartz-selective peptide sequences initially identified by phage display at pH 9 as alternative reagents for direct flotation of quartz mineral. 186 The simulation results revealed that the simultaneous presence of positively and negatively charged residues in peptide sequences are favorable for stronger binding of peptides to the surface due to two main reasons. First, the negatively charged residues have strong affinities toward abundant positively charged moieties on quartz surface at basic pH, and second, the repulsive self-interactions in the peptide chain containing dissimilarly charged residues keep the extended conformation of the peptide, guaranteeing the accessibility of peptide side groups to the surface.…”
Section: Rational Design Of Novel Ecofriendly Collectorsmentioning
confidence: 98%
“…The consideration of protonation/deprotonation states of adsorbates with pH-sensitive functional groups at different pK a is not sufficient to model adsorption phenomena at different pHs. 186 For solid molecular modeling (particularly molecular dynamics simulations) at different pH, the mineral surface and solution must also be carefully constructed. The type and area density of surface groups upon solvation, the likely ionization degree as a function of pH, the ionic strength and type of cations, etc.…”
Section: Principle Features Of Interactionsmentioning
confidence: 99%
See 2 more Smart Citations